The Influence of Religiosity and Honesty on Students’ Ghosob Behavior at Bina Umat Islamic Boarding School Yogyakarta - Fanani Murti, Akhmad; Akif Khilmiyah; Abdus Salam Muharam (Universitas PGRI Yogyakarta, 2026)
This study examines the influence of religiosity and honesty on ghosob behavior in students at the Bina Umat Islamic Boarding School in Yogyakarta. Using a quantitative approach, data were collected via a Likert-scale questionnaire from 100 male students aged 15–18 years. Religiosity is measured using Glock & Stark's five dimensions (ideological, ritualistic, experiential, intellectual, and consequential), while honesty is assessed across three domains (toward oneself, others, and God). Multiple linear regression analysis showed that both religiosity (β = 0.239, p < 0.001) and honesty (β = 0.699, p < 0.001) significantly influenced ghosob behavior, with a combined contribution of 76.5% (Adj. R² = 0.765). Honesty was the dominant predictor, accounting for 73.6% of the variance, compared with religiosity (49.8%). The findings show that despite high religiosity, ghosob behavior still occurs because it is normalized in the pesantren culture. The results of the study support Glock & Stark's theory of religiosity, Kohlberg's theory of moral development, and Bandura's theory of social learning, while emphasizing the importance of internalizing the value of honesty as a practical expression of religiosity in character education in the pesantren environment. Keywords: religiosity, honesty, ghosob behavior, pesantren, character education, psychology of Islamic education